Accounting for Waste by the Zimbabwean Gold Mining Sector - Nyakuwanika, Moses; van der Poll, Huibrecht Margaretha; van der Poll, John Andrew (The Journal of Accounting and Management, 2025)
The disposal of gold mining waste is a major cause of land degradation and forest loss in Zimbabwe. Although the mining sector is a key driver of the Zimbabwean economy, substantial volumes of wastewater, waste rocks, tailings, and slag are produced. The research aimed to establish how the Zimbabwean gold mining sector accounts for waste. Twelve in-depth interviews were conducted among selected key gold mines in Zimbabwe. It was found that some gold mines adopted international environmental accounting standards as strategies to minimise waste and move towards zero waste generation, and that waste can be converted into economic value. However, most solutions were found to be sectoral. It is recommended that holistic approaches are needed to address the challenges of waste management within the gold mining sector of Zimbabwe. Raw materials should be utilised effectively, and waste reduced to facilitate profit generation by the mining sector. Considering the potential conflicts of gold mining, we suggest a comprehensive, integrated waste management strategy consistent with other land uses. Remedial action is recommended to protect the environment. Future research may investigate ways to minimise waste through environmental management accounting practices. Interdisciplinary research may also assist as the challenges cut across several disciplines, such as accounting for the financial flows of waste and engineering for the physical flows of waste.